Relationship Between Hand Soap Use and Incidence of Contact Dermatitis in Healthcare Workers: A Literature Review - Setiawan, Reza Pahlevi Ramadhani Arfindra; Pudjiastuti, Agustina Tri (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Contact dermatitis is an inflammatory skin condition caused by direct exposure to irritant chemicals or allergens. It is classified into two main types: irritant contact dermatitis (ICD) and allergic contact dermatitis (ACD). ICD results from direct skin damage caused by chemicals without involving an immune response, while ACD is triggered by an allergic reaction involving T-cell activation and cytokines. Factors such as duration, intensity, and frequency of exposure, as well as individual skin conditions, influence the severity of dermatitis. Among healthcare workers, the prevalence of contact dermatitis is high due to frequent exposure to soaps, hand sanitizers, latex gloves, and masks containing irritants and allergens. Research indicates that up to 74.5% of healthcare workers report experiencing occupational skin reactions. Preventing contact dermatitis among healthcare workers requires careful risk management and the use of appropriate protective equipment.